Construction and validation of sample exercises on inference making for second year high school students - Lagunay, Aster D. 1947- (1977)
This research paper presents a 60 item sample inferential reading test patterned after the RFU Skill Builders. It is designed to determine a second year student's ability to comprehend reading and from judgments from some habit of mind on the basis of infering. To select students reading at grade eight level, the Gates Reading Survey Test Form I was administered to 203 students. Each item was scrutinized and reviewed for possible improvement or revision. The retained items were arranged according to difficulty level, form the easiest to the most difficult.
"October, 1977."
Vita.
Thesis (M.A.T. Reading)--University of the Philippines, Diliman.
Keywords: Reading (Secondary) -- Philippines -- Makati City; Reading -- Ability testing -- Philippines -- Makati City; Reading -- Philippines -- Makati City -- Aids and devices